Aspects of the growth of Microcystis aeruginosa on dyes and its bioremediation potential in textile effluents - Lira, Vivian Silva [UNESP]; Silva, Janete da [UNESP]; Moreira, Ingritt Caroline; Ramos, Priscilla [UNESP]; Bagatini, Inessa Lacativa; Francisco, Renata Fracácio [UNESP] (My University, 2024)
Given the textile sector's intense economic activity, its effluents are known to contribute to water quality degradation, with ecological and ecotoxicological implications. This study aimed to evaluate the influence of pure textile dyes (tartrazine yellow and indigo blue) on the growth of the cyanobacterium species Microcystis aeruginosa through direct and indirect methods. Furthermore, it aimed to verify whether this species has bioremediation potential in effluents contaminated with dyes through ecotoxicological evaluation and color reduction. Therefore, we added an inoculum of 3x103 cells/mL of M. aeruginosa to a concentration of 500 mg/L of each pure dye in solutions with WC medium. sThey remained in direct and indirect light for seven days, and the number of cells was evaluated over 168 hours. Then, we collected two types of effluents representative of the dyes studied (jeans factory blue dye and carpet factory yellow dye), which remained raw and diluted by 50%. We added an inoculum of 8.64x103 ± 93 cells/mL of this cyanobacterium to each effluent. Moreover, we added a control without inoculum for each condition. Aeration remained constant for 25 days. We conducted ecotoxicological evaluations of the effluents (before and after 25 days of bioremediation) through seven-day assays with the larvae of Danio rerio, verifying survival and growth parameters. The results showed that the cyanobacterium grew significantly in direct contact with the tartrazine yellow dye (1.49x105 ± 1910 cells/mL). However, growth was reduced with both dyes in indirect contact, and there was total inhibition with indigo blue in direct contact, significantly differing from the control. After 25 days, the number of cells in the effluents diluted by 50% decreased compared to the inoculated amount. Considering the color reduction in the carpet factory effluent (100%), the presence of cells enabled a 43% reduction, and in the only aerated condition, 34.6% decolorization. Thus, considering the greater color degradation in the presence of cyanobacteria in this effluent, we believe that cell growth and active metabolism occurred before the 25 days tested. The color removal percentages in the presence of cells did not reduce toxicity. Therefore, we concluded that M. aeruginosa has the potential to grow in high concentrations of tartrazine yellow (500 mg/L).
Keywords: Bioremediation; Carpets; Cyanobacteria; Danio rerio; Jeans; Textile dyes